Effects of access to radiology in out-of-hours primary care on patient satisfaction and length of stay. Issue 1 (1st January 2021) - Rutten, Martijn H.; Giesen, Paul H. J.; Assendelft, Willem J. J.; Westert, Gert; Smits, Marleen
Abstract: Background: Direct access to hospital radiology facilities by general practitioner (GP) cooperatives is known to decrease the number of emergency department referrals, but the effects on length of stay (LOS; time from patient arrival at GP cooperative till departure to home) and patient experiences are unclear. Objectives: To provide insight into the LOS and experiences of trauma patients with an indication for radiology at GP cooperatives with and without access to radiology. Methods: A multi-methods observational study in April 2014–October 2015 at six GP cooperatives in The Netherlands, covering three organisational models for access to radiology: no direct access, limited access and unlimited access. Patient experiences were measured with a questionnaire. Patient records were analysed for background characteristics, radiology outcomes, referral and LOS. Results: In total 657 patients were included, 232 no direct access model, 307 limited access model and 118 unlimited access model. The mean LOS was 99 minutes, with a significant difference between GP cooperatives without access to radiology (121 minutes), with limited access (86 minutes), and with unlimited access (90 minutes). The differences were larger for patients without radiological abnormalities. On a ten-point scale, patients rated GP cooperatives with unlimited access to radiology higher (8.62) than those without access (8.36) or with limited access (8.39). Conclusion: Access to radiology by GP cooperatives seems to reduce the length of stay and is slightly more appreciated by patients. GP cooperatives with unlimited access seem to provide the most efficient and best-valued care, contributing to more patient-centred care.